2018
DOI: 10.1002/macp.201800124
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Transition of Dual‐Responsive ABC Terpolymer in Water: Effect of Hydrophobic Block

Abstract: To reveal the importance of hydrophobic block in morphology transition of responsive copolymers, four well‐defined ABC terpolymers with the same poly(dimethylamino ethyl methacrylate) (PDMAEMA) and PEG segments are synthesized by sequential RAFT polymerization. Poly (n‐hexyl methacrylate) (PnHMA), poly(n‐butyl methacrylate) (PnBMA), poly(ethyl methacrylate) (PEMA), and poly(methyl methacrylate) (PMMA), with glass transition temperatures of −5, 20, 65, and 100 °C, respectively, are selected as hydrophobic segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(124 reference statements)
1
4
0
1
Order By: Relevance
“…Nevertheless, the FESEM indicated that both 6a and 6b self‐assembled into spherical micelle in DI water at temperatures below the T cp . Spherical micelle self‐assembled from thermoresponsive block copolymers have also been revealed in previous reports . The diameters of different polymer systems are distinct which is highly related to the structure parameters as well as solution conditions.…”
Section: Resultssupporting
confidence: 52%
“…Nevertheless, the FESEM indicated that both 6a and 6b self‐assembled into spherical micelle in DI water at temperatures below the T cp . Spherical micelle self‐assembled from thermoresponsive block copolymers have also been revealed in previous reports . The diameters of different polymer systems are distinct which is highly related to the structure parameters as well as solution conditions.…”
Section: Resultssupporting
confidence: 52%
“…Amphiphilic copolymers containing ionizable groups such as carboxylic acids and amines form aw ide range of selfassembled structures in response to changes in pH. [4][5][6] Tr ansitions from unimeric solutions to spherical micelles are common, [7,8] while with careful control of the hydrophilichydrophobic balance of the copolymer, transitions from spherical micelles to wormlike micelles [9][10][11] and/or vesicles [12][13][14][15] may also be observed.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were heated from room temperature to 220°C under air atmosphere. According to the DSC results, the glass transition temperature ( T g ) [39] of the samples are summarised in Table 2. Since silica aerogel nanoparticles do not bear any transitions in this range of temperature, therefore only the thermal transition of copolymers is observed.…”
Section: Resultsmentioning
confidence: 99%